BENTUK-BENTUK INVESTASI DAN PENGARUHNYA TERHADAP PENYERAPAN TENAGA KERJA DI INDONESIA - Jamaludin , Jamaludin; Tradesa, Anggi Purnama; Adelia , Nanda (AL-BALAD : Jurnal Hukum Tata Negara dan Politik Islam, 2024)
This research was conducted with the aim of: 1) To determine the forms of investment and their influence on labor absorption in Indonesia. 2) To find out the factors that influence investment in Indonesia. The type of research used in this research is normative legal research using statutory and conceptual approaches. The results of this research show that: 1) forms of investment include: Public Investment, Private Investment, Gross Investment, Net Investment, Domestic Investment, Foreign Investment, Induced Investment and Antonomous Investment. 2) Factors that influence investment include: interest rates, the predicted level of investment profits, the level of national income and its changes, profits obtained by companies, the political situation, technological progress and conveniences provided by the government. A high level of investment will increase production capacity which ultimately leads to the opening of new jobs. That way, the unemployment rate can be reduced and people's income can increase. Investment also allows for the transfer of technology and knowledge from developed countries to developing countries. Apart from investment, wages also have a relationship with labor absorption. For most workers, this minimum wage has no effect, because they enjoy wages above the minimum wage.